Challenges and Opportunities in the Global Dissemination of Chinese Traditional Culture in the New Media Era - Zhao, Jingyi (Transactions on Social Science, Education and Humanities Research, 2024)
This paper explores the challenges and opportunities that Chinese traditional culture faces in the global dissemination process during the new media era. By analyzing the impact of new media technologies on cultural communication, the paper highlights how these technologies can both support and hinder the global spread of traditional Chinese culture. The study uses a combination of literature review and case studies to examine the key factors influencing the effectiveness of cultural dissemination and proposes strategies for overcoming obstacles while maximizing the benefits offered by new media platforms.